Van Gogh, Cowper, and Unfinished Suffering: Narrative Hope in Clinical Chaplaincy - Hyewon Kim (Journal of Pastoral Care & Counseling: Advancing theory and professional practice through scholarly and reflective publications, 2026)
This clinical pastoral reflection explores how historical and artistic narratives may support meaning-making in chaplaincy encounters. During a pastoral visit with a patient experiencing advanced cancer and depression, the lives of Vincent van Gogh and William Cowper became interpretive resources through which suffering was reframed as spiritually continuous rather than spiritually disqualifying. The encounter illustrates how narrative engagement can foster renewed hope while suffering remains unresolved within clinical pastoral care.